Analisis Kesalahan Berbahasa Jawa sebagai Upaya Pemertahanan Bahasa Daerah Sesuai Kaidah - Kartika Sari, Fitriana; Pramudiyanto, Ahmad; Ita Dhamina, Serdaniar (Program Studi Sastra Jawa, Fakultas Bahasa dan Seni, Universitas Negeri Semarang, 2024)
There are still many Javanese language errors found in student narrative essays, even though the use of language according to the rules is one of the efforts to preserve the local language. The approach used is descriptive qualitative case study combined with the theory of Javanese language error analysis. The research data is in the form of narrative essays in Javanese ngoko variety of students that contain Javanese language errors. Data collection techniques used listening, note-taking and observation techniques. Data analysis used interactive model. The results showed that: 1) there are 4 language errors at the level of phonology, namely 75% errors in writing vowel phonemes, 20% errors in writing consonant phonemes, 2% errors in adding consonants, and 3% errors in subtracting consonants; 2) there are 5 language errors at the morphological level, namely errors due to the writing of prefixes separated from the base word as much as 25%, errors due to the writing of suffixes separated from the base word as much as 21%, affixing errors as much as 22%, errors in writing ater-ater anuswara as much as 9%, and diction errors as much as 23%; 3) Analysis of Javanese language errors can be implemented as an effort to preserve local language according to the rules in the realm of Javanese language learning; 4) In an effort to preserve the local language according to the rules, it is necessary to have a Javanese Language Error Analysis course.